Cervical lymph node metastasis as the first and only manifestation of prostatic adenocarcinoma - Tadashi Terada, MD, PhD (Elsevier, 2015)
Prostatic carcinoma initially manifesting as only cervical lymph node swelling is a rare phenomenon. A 74-year-old man presented left cervical lymphadenopathy. An excisional biopsy was performed, and it was pathologically diagnosed as metastatic thyroid follicular carcinoma. However, imaging technique revealed no thyroid tumor or tumor in the body. The lymph node was re-examined 23 months after the first diagnosis: it showed adenocarcinoma positive for PSA and PSAH. Biopsy of the prostate was performed immediately, and it showed Gleason 8 (4 + 4) prostatic adenocarcinoma. Imaging technique showed two small metastases to pelvic bone. No other metastatic lesions were detected. The patient later developed acute myelogenous leukemia, and died of respiratory failure. The present case shows that prostatic adenocarcinoma can present only cervical lymph node swelling without metastases to other organs.